The Operation of Stenographic Discourse in Contemporary Theatrical Performance - Ahmed, Basim Muhammad (Journal of Tikrit University for Humanities, 2024)
There is no doubt that arts have a material form which the aesthetic achievement is built upon. Therefore, the researcher found that the art of theater, especially the performance whose artistic achievement is based on discourse, provides a language embodied in scenography. Therefore, the researcher decided to study this work in the scenography of theatrical discourse, and divided the study into four sections. In the first section, the research problem was defined in the following question: (What is the function of scenography discourse in contemporary theatrical performance?). Therefore, this is considered of cognitive importance as it provides an objective study for researchers in theatrical sciences at the level of design and direction, in addition to the goal of the research (revealing the function of scenography discourse in Contemporary theatrical performance). The first section ended with defining the terminology. In the second section the theoretical framework as it included two sections. The first section dealt with the researcher (concepts of scenography) from a general standpoint, and the second section (the experience of the scenography director) and how this technical and physical work was coupled with theatrical art. The section is concluded with the most important indicators that resulted from the theoretical framework.The third section included the procedures and consisted of the research community, which included the intentional research sample, the research tool, and the analysis of the sample. The fourth section included the results, conclusions, recommendations, and proposals.